Optimal Replication of Contingent Claims under Portfolio Constraints - Broadie, Mark; Cvitanić, Jakša; Soner, H. Mete (Review of Financial Studies, 1998)
Constraints on the gamma of the replicating portfolio, constraints on portfolio amounts, and constraints on the number of shares are also considered.